2021
DOI: 10.1007/s11846-021-00457-w
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and new venture performance in emerging markets: the mediating role of opportunity recognition

Abstract: How entrepreneurial orientation facilitates the identification of new opportunities in newly established ventures in emerging economies remains largely unexplored. Approaching entrepreneurial orientation as a second order latent construct, we examined the mediating role of opportunity recognition on new venture performance. Using a survey data from 316 SMEs, the results of the analysis in SmartPLS highlights that entrepreneurial orientation indirectly contributes to the performance of new ventures, where the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 139 publications
(181 reference statements)
7
81
0
Order By: Relevance
“…Therefore, new ventures should capture the changes and trends in the institutional environment in real time to provide a sustained impetus for the implementation of enterprise-oriented strategic decisions. Entrepreneurial orientation brings innovation, proactiveness, and risk-bearing, characteristics which help new ventures grasp market opportunities [54], quickly identify and develop entrepreneurial opportunities, and enhance the willingness of companies to take risks when they carry out innovative practices. Improving their ability to innovate helps new ventures gain a competitive advantage in a highly competitive market environment.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Therefore, new ventures should capture the changes and trends in the institutional environment in real time to provide a sustained impetus for the implementation of enterprise-oriented strategic decisions. Entrepreneurial orientation brings innovation, proactiveness, and risk-bearing, characteristics which help new ventures grasp market opportunities [54], quickly identify and develop entrepreneurial opportunities, and enhance the willingness of companies to take risks when they carry out innovative practices. Improving their ability to innovate helps new ventures gain a competitive advantage in a highly competitive market environment.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Wei et al (2019) have found that political skills and entrepreneurial opportunity recognition not only play a mediating role in entrepreneurial education and innovation but also have a chain mediation effect on the relationship between entrepreneurial education and innovation. Studies also indicate that opportunity recognition plays a mediating role between entrepreneurial orientation and the performance of the new business (Anwar et al, 2021). Therefore, this study proposes Hypothesis 3: The entrepreneurial opportunity recognition of college students plays a mediating role in the impacts of internal locus of control on entrepreneurial intention.…”
Section: Entrepreneurial Opportunity Recognition Plays a Mediating Ro...mentioning
confidence: 84%
“…Studies have found that entrepreneurial alertness has a positive impact on opportunity recognition, improving the individual's awareness of obtaining information and possibilities to identify opportunities (Hajizadeh & Zali, 2016). Some studies have found that entrepreneurial alertness and entrepreneurial opportunity recognition play an important mediating role between personality variables and entrepreneurial intentions (Anwar et al, 2021;Hu et al, 2018;Yan et al, 2018;Yasir et al, 2020). Subsequently, college students strengthen their entrepreneurial alertness; their entrepreneurial opportunity recognition ability is also significantly improved.…”
Section: The Chain Mediation Effects Of Entrepreneurial Alertness And...mentioning
confidence: 99%
“…To avoid common method bias as much as possible and similar to comparable survey studies (e.g., Anwar et al 2021;Aschauer et al 2015;Muñoz-Pascual et al 2021), we followed the procedures suggested by Podsakoff et al (2003). First, we ensured the respondents that we guaranteed their anonymity.…”
Section: Sample and Research Designmentioning
confidence: 99%